(untitled) (Journal of Nepal Geological Society, 1995)
The Cambrian sequences of Spiti basin are exposed in Pin-Parahio valleys and in the Kunzum La Takche section. They pass conformably downward into a thick sequence of Late Precambrian rocks. Various faunal assemblages have been recorded from these sequences; characteristic faunal gaps occur in the lower part of Lower Cambrian, lower Middle Cambrian and in Upper part of Middle and Upper Cambrian. These gaps are represented by barren zones. In Pin-Parahio sections the uppermost part of the Cambrian is marked by an angular unconformity but in Kunzun La section this unconformity is not as apparent as in Pin-Parahio, but the change in lithology is very prominent. This paper discusses the position of intra system boundaries and the affinities of the fauna with other Cambrian sequences. It has been observed that the Middle and Upper Cambrian fauna contains elements similar to that found in Australia and Indochina and resemble other cosmopolitan genera.